FACTORS AFFECTING COTTON PRODUCTION DECISIONS OF FARMERS: EASTERN MEDITERRANEAN REGION, TURKEY - M. Emin BİLGİLİ; Hilal YILMAZ; Selcan AKKOYUN; Yasemin VURARAK; Mevlüt GÜL (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study aimed to determine the factors affecting cotton production decisions of producers in the Eastern Mediterranean Region of Turkey. The main research material was the data obtained from the questionnaires conducted with farmers in this region. We identified six factors influencing the decision-making in cotton production, which included economic, technical, political, environmental, personal, and product-related factors. The logistic regression model attempted to explain the factors convincing farmers to cultivate cotton. The variable related to the cotton experience of farmers was found significant. Besides, the variables of the number of individuals per household, total agricultural area, cotton plantation area in 2013, 2011, 2000, and 1990 were statistically significant. Cotton cultivation areas in the Eastern Mediterranean region tended to shrink rapidly after 2000s. In addition to increasing the cost of cotton production, factors like competitor product costs, productivity, changes in technology and price fluctuations also played a role in such a decline. Therefore, the decision to cultivate cotton is affected by not only the price of cotton but also the government supports in place, changes in foreign trade practices, technology, human resources, competitor product prices, and yield.